SISTEM INFORMASI DAN PENGOLAHAN DATA KRIMINAL DI POLRES PASAMAN BARAT DENGAN AKSES VIRTUAL HOST BEBASIS CLIENT SERVER MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN DATABASE MYSQL - Larissa Navia Rani; Hari Marfalino; Putri Asysyura Yuska (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2019)
The rapid development of computer technology and information greatly helps work in storing, accessing to data processing becomes faster and easier, this has triggered various fields in utilizing this with the use of computer-based information systems, especially for intelligence units in western security police. The system that will be created uses access to the virtual host-based client server. Modeling used UML modeling, this system is built using PHP programming language and MYSQL database. The results of the study show that the information system designed can process criminal data and is able to be implemented at the research site..